Gender Inequality on the Uses of the Internet: A Study of Dhaka City of Bangladesh - Alam, Jahangir (European Scientific Journal, ESJ, 2020)
Nowadays, the internet is considered a basic need, and for this, many researchers and academicians are engrossed by this subject. Very few literary works have been found to show gender inequality on the internet uses. For this reason, this study has been conducted. The main objective of this study is to assess the extent of gender inequalities on the uses of the internet in terms of time spends, money spends, data download, data upload, time spends on Social Networking Sites, time spends per access, and online earnings. For conducting this study, a survey questionnaire has been used for collecting primary data. Six hypotheses are developed and tested at a 5% level of significance. Results of the study indicate that there is significant inequality that exists between males and females in terms of time spends on the internet; money spends on the internet, the volume of data download and upload, time spends on social networking sites. Besides exists, an insignificant inequality between males and females in terms of time spends on the internet per access. The study recommends that female internet users need to be more thoughtful in case of information access, online earnings, and internet-based government and semi-government services. Based on the findings, the paper recommends that women need awareness on online earnings, online-based government services, and how effectively they can use information. This study suggests ensuring proper uses of the internet for both males and females equally to make Bangladesh competent.